Mechanism of Synergy Between Tetracycline and Quercetin Against Antibiotic Resistant Escherichia coli - Qu, Shaoqi; Dai, Cunchun; Shen, Zhangqi; Tang, Qihe; Wang, Haixia; Zhai, Bing; Zhao, Li; Hao, Zhihui (Frontiers in Microbiology, 2019)
Treatment of multi-drug resistant (MDR) Escherichia coli intestinal infections are being hampered by the presence of the mcr-1 (colistin) and tet (tetracycline) resistance genes in these strains. We screened 7 traditional Chinese medicines for their ability to synergize with tetracycline to provide an effective new drug for the treatment of animal intestinal diseases caused by MDR E. coli. Our primary screen identified quercetin as a compound that reduced the minimum inhibitory concentration (MIC) of tetracycline against the E. coli standard test strain American Type Culture Collection (ATCC) 25922 and clinical isolates 4-fold from 4 and 256 μg/mL to 1 and 64 μg/mL, respectively. Low levels of quercetin in combination with tetracycline were bactericidal for clinical E. coli isolates and after 24 h, the differences between this combination and each drug singly were 108 CFU/mL. We used this combination therapy in a mouse infection model and found 100% survival after 48 h compared with <50% for each drug alone. This drug combination also synergized to disrupt the bacterial cell envelope resulting in increased permeability and cell lysis. These data demonstrate that combinatorial screening at low concentrations constitutes an efficient approach to identify clinically relevant quercetin/tetracycline combinations and is a valuable prototypical combination that has a high clinical potential against E. coli infections.